Physics and philosophy - Feyerabend, Paul 1924-1994 (Feyerabend, Paul, 1924-1994. Philosophical papers, 2016)
This collection of the writings of Paul Feyerabend is focused on his philosophy of quantum physics, the hotbed of the key issues of his most debated ideas. Written between 1948 and 1970, these writings come from his first and most productive period. These early works are important for two main reasons. First, they document Feyerabend's deep concern with the philosophical implications of quantum physics and its interpretations. These ideas were paid less attention in the following two decades. Second, the writings provide the crucial background for Feyerabend's critiques of Karl Popper and Thomas Kuhn. Although rarely considered by scholars, Feyerabend's early work culminated in the first version of Against Method. These writings guided him on all the key issues of his most well-known and debated theses, such as the incommensurability thesis, the principles of proliferation and tenacity, and his particular version of relativism, and more specifically on quantum mechanics.